2015
DOI: 10.1007/s00216-015-8496-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hypothalamic neurotransmitter and prostanoid levels in response to NMDA, CRF, and GLP-1 stimulation

Abstract: Determination of neuroactive substances, such as neurotransmitters and prostanoids, in the extracellular space of the living brain is a very important technique in neuroscience. The hypothalamic paraventricular nucleus (PVN) is one of the most important autonomic control centers in the brain. Recently, we demonstrated that thromboxane (Tx) A2 in the PVN may play an important role in adrenomedullary outflow evoked by N-methyl-D-aspartate (NMDA), corticotrophin-releasing factor (CRF), and glucagon-like peptide-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Perfusion of the PVN with NMDA increased, in a manner sensitive to MK801, the local level of thromboxane B 2 (the inactive metabolite of TXA 2 ), glutamate and GABA, the plasma level of catecholamines (Okada et al 2000; Kondo et al 2015) and BP (Li and Pan 2007). We confirmed that microinjection of NMDA into the PVN increased BP and HR (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Perfusion of the PVN with NMDA increased, in a manner sensitive to MK801, the local level of thromboxane B 2 (the inactive metabolite of TXA 2 ), glutamate and GABA, the plasma level of catecholamines (Okada et al 2000; Kondo et al 2015) and BP (Li and Pan 2007). We confirmed that microinjection of NMDA into the PVN increased BP and HR (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotransmitters (5-HT, GABA, Ach, and histamine) in PVN microdialysates were analyzed according to our previously published methods 47,51 by LC-ITMS n analysis. To measure neurotransmitter concentrations in the dialysates, the peak area ratio relative to an internal standard was calculated and determined from the corresponding calibration curve.…”
Section: Measurement Of Neurotransmitters In Pvn Microdialysatesmentioning
confidence: 99%
“…The concentration of neurotransmitters reflects the status of the central nervous system [ 11 , 12 , 13 ]. In recent years, ultra-high performance liquid chromatography coupled with triple quadrupole mass spectrometry (UPLC-QqQ-MS/MS) has been used for the comprehensive determination of neurotransmitters, with high sensitivity and efficiency [ 14 ].…”
Section: Introductionmentioning
confidence: 99%